2009
DOI: 10.1016/j.wear.2008.12.066
|View full text |Cite
|
Sign up to set email alerts
|

HVOF-sprayed WC–CoCr coatings on Al alloy: Effect of the coating thickness on the tribological properties

Abstract: a b s t r a c tThe microstructure, the micromechanical properties, the wear behaviour and the impact resistance of WC-CoCr cermet coatings, deposited onto an aluminium alloy substrate by High Velocity Oxygen-Fuel (HVOF) flame-spraying, were examined as a function of the coating thickness, which was varied between 50 m and 150 m by performing different numbers of scans of the HVOF torch in front of the substrate. The coatings became denser and significantly harder as the number of torch scans increased: the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 43 publications
5
45
0
1
Order By: Relevance
“…In an open literature, WC-Co family coatings sprayed by HVOF process have hardness in the range of 900-1500 HV. The hardness of all coatings in the present study is in agreement with the reported literature [11,14].…”
Section: Resultssupporting
confidence: 92%
“…In an open literature, WC-Co family coatings sprayed by HVOF process have hardness in the range of 900-1500 HV. The hardness of all coatings in the present study is in agreement with the reported literature [11,14].…”
Section: Resultssupporting
confidence: 92%
“…Also bond coats may be used because of the mismatch between coating and substrate material. HVOF WC-CoCr cermet coatings on aluminum substrate could be used for plastic injection moulds due to high hardness, low sliding wear, low porosity, and good endurance against impacts [78]. MoCoB-Co/Cr cermet coating could be used for protection of glass sheet forming moulds because it has excellent high temperature properties, such as low friction coefficient to glass, oxidation resistance, and low mechanical abrasion [79].…”
Section: Applications Of Hvof Coatingsmentioning
confidence: 99%
“…The deposition process involves spraying molten or semi-molten powder particles at high velocities onto the substrate surface [5]. The high kinetic energies generated by the spraying process result in a very dense coating that is well bonded to the substrate and resistant to mechanical wear and corrosion [6][7][8][9][10][11], with particle size being a key factor in the coating density achieved [12].…”
Section: I In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%